Infrared and Raman Spectra, Ab Initio Calculations, Force Field Refinement and Vibrational Assignment of 3-Aminophenol - Büyükmurat, Y.; AKYÜZ, SEVİM (Elsevier, 2005)
The molecular geometry and molecular vibrations of 3-aminophenol and its some deuterated derivatives have been investigated with the aid of quantum chemical calculations, normal coordinate analysis using force field refinement method and vibrational spectroscopy. The barrier of the OH group pointing in the direction of the amino group with respect to the anti conformer for 3-aminophenol was computed to be 2.44 kJ/mol. The spectroscopic and theoretical results are compared to the corresponding properties for some similar molecules.
Keywords: Ab Initio Calculations; Aminophenol; Force Field Refinement; Nfrared and Raman Spectra